First expression:
5(x+4)+3(x+2) = 5x + 20 + 3x + 6
Expanding: 5x + 20 + 3x + 6 = 5x + 3x + 20 + 6 = 8x + 26
Second expression:
4(x+3)+2(x-4) = 4x + 12 + 2x - 8
Expanding: 4x + 12 + 2x - 8 = 4x + 2x + 12 - 8 = 6x + 4
Third expression:
4(x+2)+2(x+5) = 4x + 8 + 2x + 10
Expanding: 4x + 8 + 2x + 10 = 4x + 2x + 8 + 10 = 6x + 18
Answer choices:
8x + 26
6x + 4
6x + 18
Therefore, the expressions expanded and simplified are:
1) 8x + 26
2) 6x + 4
3) 6x + 18
So the correct answer is 8x + 26, 6x + 4, and 6x + 18.
expand the expressions and simplify.
5(x+4)+3(x+2) =
4(x+3)+2(x-4) =
4(x+2)+2(x+5)=
answer choices:
6x+18
8x+4
8x+26
6x+4
7x-18
7 answers
which of the answer choices go with 5(x+4)+3(x+2) =
The answer choice that goes with 5(x+4)+3(x+2) = 8x + 26.
4(x+3)+2(x-4) =
what about this one?
what about this one?
The answer choice that goes with the expression 4(x+3)+2(x-4) = 6x + 4.
and this one?
4(x+2)+2(x+5)=
4(x+2)+2(x+5)=
The answer choice that goes with the expression 4(x+2)+2(x+5) = 6x + 18.